IMPLEMENTASI KEBIJAKAN BANTUAN OPERASIONAL SEKOLAH DAERAH (BOSDA) DI SEKOLAH MENENGAH PERTAMA NEGERI 02 KABUPATEN MALINAU - Yusri Yusri (Jurnal Paradigma (JP), 2019)
The purpose of this study was to describe and analyze the Implementation of District School Operational Assistance Policy (BOSDA) at Junior Secondary School 02 Malinau City. The research method used is descriptive qualitative. The data analysis used is the interactive data model. The result of the research, it can be concluded that Operational Assistance Policy of School Area in Junior Secondary School of State 02 Malinau as regulated in Decision of Regent of Malinau Number 25 year 2014, immensatively less than optimal, because confronted by various obstacles. Keywords: Implementation, Policy, School Operational Assistance